2020
DOI: 10.1186/s12864-019-6444-0
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of Pinus pinaster under Fusarium circinatum challenge

Abstract: Background: Fusarium circinatum, the causal agent of pitch canker disease, poses a serious threat to several Pinus species affecting plantations and nurseries. Although Pinus pinaster has shown moderate resistance to F. circinatum, the molecular mechanisms of defense in this host are still unknown. Phytohormones produced by the plant and by the pathogen are known to play a crucial role in determining the outcome of plant-pathogen interactions. Therefore, the aim of this study was to determine the role of phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 123 publications
(153 reference statements)
5
34
1
Order By: Relevance
“…In previous studies, a marked trend has been observed in the increase in DEGs as the disease was progressing [ 29 , 38 , 42 , 45 ]. The transcriptomic comparison of the present study at an early stage of disease (4 dpi) showed that the number of DEGs in P. pinea (1822) was vastly higher than in P. radiata (371).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In previous studies, a marked trend has been observed in the increase in DEGs as the disease was progressing [ 29 , 38 , 42 , 45 ]. The transcriptomic comparison of the present study at an early stage of disease (4 dpi) showed that the number of DEGs in P. pinea (1822) was vastly higher than in P. radiata (371).…”
Section: Discussionmentioning
confidence: 96%
“…MeJA-mediated cellular responses include the induction of genes encoding terpene synthases [ 63 ] and enzymes of the JA biosynthesis such as LOX [ 64 ], both widely up-regulated in the two pine species. Although these results could indicate an active biosynthesis of JA mainly in P. pinea , the down-regulation of COI1 together with the high induction of JAZ genes could denote a suppression of JA signaling, as observed in P. pinaster infected with F. circinatum at 5 and 10 dpi [ 42 ]. Our results further support that F. circinatum may target and block JA signaling by COI1 suppression as hypothesized by Hernandez-Escribano et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations